2008
DOI: 10.1111/j.1440-172x.2008.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endometriosis on work and social participation

Abstract: Endometriosis is a debilitating chronic disease that can affect many aspects of everyday life owing to symptoms such as pain and fatigue. This paper reports the findings of a study exploring the impact of symptomatic endometriosis on women's social and working life. The study used a feminist approach. Eighteen women were interviewed and a thematic approach used to analyse the data. The analysis is structured around three themes focusing on issues around disclosure of symptoms in the work place; the impact of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 15 publications
10
103
0
1
Order By: Relevance
“…Fourquet et al [16]. also found that women had SF-12 scores denoting statistically significant disability in physical and mental health components, indicating that the women in this study experienced substantial disability and Nnoaham et al [18] found that women with endometriosis had reduced physical health compared with the normative population. Sleeping has also been found to be negatively affected by endometriosis Fourquet.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Fourquet et al [16]. also found that women had SF-12 scores denoting statistically significant disability in physical and mental health components, indicating that the women in this study experienced substantial disability and Nnoaham et al [18] found that women with endometriosis had reduced physical health compared with the normative population. Sleeping has also been found to be negatively affected by endometriosis Fourquet.…”
Section: Discussionmentioning
confidence: 93%
“…Pain is consistently reported as a central and destructive feature of life with endometriosis and several studies report a negative correlation between pain and QoL Sepulcri et al [24], Nnoaham et al [18], Souza et al [25], Tripoli et al [23]. Endometriosis symptoms, and specifically pain, have a detrimental impact on daily life and physical functioning (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several quantitative studies describing symptoms however, little qualitative research has been conducted (Ballard, Lowton, & Wrigt, 2006;Cox, Henderson, Andersen, Cagliarini, & Ski, 2003;Gylmour, Huntington, & Wilson, 2008). Specifically one focusing on women's pain experience -and much of what exists lacks rigour in key areas (Denny & Khan, 2006).…”
Section: New Perspectives On Endometriosis Treatmentmentioning
confidence: 99%